ANALISIS PEMBENTUKAN KECAMATAN BARU DI KOTA MADIUN UNTUK MENINGKATKAN PELAYANAN KEPADA MASYARAKAT - Tarandeli, Rizka Ramadhani; Isharyanto, Isharyanto (Res Publica: Jurnal Hukum Kebijakan Publik, 2018)
This article aims to analyze and examine the setting up of new kecamatan formation in Madiun City based on Government Regulation Number 19 Year 2008 regarding Subdistrict as well as the establishment of new districts in Madiun City. This empirical legal research is descriptive with the location of research at the Central Bureau of Statistics of Madiun City, Village Monograph from the Governmental Section Madiun City. Types and sources of research data include primary and secondary data. Data collection techniques through interviews and literature study. Data analysis technique is done qualitatively with interactive model analysis. The results of this study explain that the formation of new sub-districts in Madiun City must meet some of the requirements contained in Government Regulation Number 19 Year 2008, in Article 3, the formation of sub-districts as referred to in Article 2 must meet the three conditions that become the benchmark in the formation of new kecamatan. The terms in question are administrative requirements, technical requirements, and physical conditions of the territory.